PENERAPAN RAPID APLICATION DEVELOPMENT (RAD) DALAM PEMBUATAN SISTEM INFORMASI MARKETPLACE PENYEWAAN MOTOR DAN MOBIL - saifudin; Atika Indah Rahadyanti Prasetya (Informatics and Computer Engineering Journal, 2021)
Along with the development of information technology and innovation, systems thinkers have delivered business organizations to work more effectively and efficiently than ever before. The android and computer systems are tools that were created to facilitate human work, while achieving progress both in making hardware and software. The business of renting motorbikes and cars is in need of information systems that support and provide satisfying services for customers. At present the rental service is only in the form of small entrepreneurs engaged in motorbike and car transportation rental services. The system used to find out all information available to rental entrepreneurs must conduct research that is by using software development methods and data collection techniques. This information system is the best solution to solve the problems that exist in this business, and with a computerized system can be achieved an effective and efficient activity in supporting activities in this marketplace system. A computerized system is better than a manual system to run more effectively and efficiently and the rental system is now more conducive than the previous system.